(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
When it comes to the communication of healthcare professionals, the concept of competence in this area cannot be considered a complete concept if it does not include communication that is based on empathy and is not applied using assertiveness. It can be said that empathy and assertiveness are indispensable links in the interpersonal communication of healthcare professionals, whether it is communication directed towards patients or the organizational aspect of communication. Therefore, the goal of this research was to determine whether there is a connection between empathy and assertiveness in the communication of healthcare professionals. In this paper, a systematic review of literature was conducted, as part of which the Web of Science and Scopus databases were examined, and the key words according to which the databases were searched were empathy, assertiveness, and communication. The results of a systematic literature review showed that this is a relatively unexplored area in the recent period. This paper also represents a scientific basis for research of connection between empathy and assertiveness in the communication of healthcare professionals in Croatia.